2,5-Dihydroxybenzaldehyde 4-methylthiosemicarbazone - Tan, Kong Wai (International Union of Crystallography, 2008)
The planar molecules of the title compound, C(9)H(11)N(3)O(2)S, are linked into a supramolecualr chain via O—H⋯S hydrogen bonds. These chains are connected into a two-dimensional array via N—H⋯O hydrogen bonds; an intramolecular O—H⋯N hydrogen bond is also present.